A busca pela sustentabilidade em um processo industrial: modelo de integração da técnica Seis Sigma com aspectos sociais e ambientais - Santos, José Carlos da Silva (2018)
In recent years, customers, investors and society have been looking for companies that are not only profitable, but also conscious of the environment and social responsibility. Since then, the search for the balance between economic, environmental and social dimensions has been incorporated in large companies. The literature has shown that some companies are interested not only to evaluate the level of sustainability of the company as a whole, but also to improve its processes taking into account the three dimensions of sustainability. However, sustainability assessment initiatives suffer from two limitations, that is, they only apply to assessing the sustainability of the company as a whole, or consider sustainability aspects separately, without integration, making them unsuitable for assessing and sustainability in an industrial process. In order to solve this question, this study proposed a model of integration of the Six Sigma technique with the social and environmental variables as a way to enable significant gains in the environmental, economic and social dimensions. For this, a systematic review of the literature on the topic was carried out. A model for integration of social and environmental variables was defined in the Six Sigma technique, specifically in the DMAIC method. In order to achieve this objective, it was also necessary to propose an indicator to measure the level of sustainability of an industrial process, in order to obtain a single result. To enable the application of the model proposed here to the real world situation, the proposed model was applied in a machining process of a metal mechanic company. With the results obtained through the application of the model in the machining process, it was concluded that the integration of the Six Sigma technique, specifically the DMAIC method integrated with the social and environmental variables can contribute significantly to the increase of the level of sustainability of a industrial process and, as a consequence, that of the company as a whole. As gains for the area of ​​knowledge we can highlight the integration of environmental and social variables to the Six Sigma technique (DMAIC).